Couple Beads: An Integrated Method of Natural Family Planning. (February 2016) - Mulcaire-Jones, George; Fehring, Richard J.; Bradshaw, Megan; Brower, Karen; Lubega, Gonzaga; Lubega, Paskazia
Various fertility indicators are used by natural family planning methods to identify the fertile and infertile phases of a woman's menstrual cycle: mucus observations, cycle-day probabilities, basal body temperature readings, and hormonal measures of LH and estrogen. Simplified NFP methods generally make use of a single fertility indicator such as cycle-day probabilities (Standard Days Method) or mucus observations (Billings Ovulation Method). The Couple Bead Method integrates the two simplest fertility indicators, cycle-day probabilities and mucus observations, expanding its applicability to all women, regardless of cycle regularity and length. In determining cycle-day probabilities, the Couple Bead Method relies on a new data set from ultrasound-derived determinants of gestational age that more directly define the day of conception and the fertile window. By using a visual-based system of inexpensive colored beads, the Couple Bead Method can be used by couples of all educational and income levels. Lay Summary : Natural family planning methods provide education in regard to the signs of a woman's body which indicate if she is possibly fertile or not. Two important signs are the day of her menstrual cycle and her observations of bleeding and cervical mucus or dryness. The Couple Bead Method teaches a couple how to observe these signs and chart them with a system of colored beads. The Couple Bead Method can be used by women with regular or irregular cycles. The bead sets are inexpensive and consist of a length of plastic cord, colored "pony beads" and safety pins.